Characteristics Affecting Creative Business Income of Leading Subsector Economies in Java - Purnawan, Muhammad Edhie; Taufan, Muhammad (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This study aimed to fill the literature gap on companies’ characteristics, focusing on the effects of entrepreneurs and business characteristics on the companies’ income. The companies chosen are the ones in the leading subsector, particularly the case in Java. This study also analyzed which characteristics of entrepreneurs and businesses affected income in the creative industry. The method used in this study was multiple linear regression and standardized beta test, with cross-sectional data taken from the specific survey in creative economy issued by BPS and BEKRAF in 2016. The unit of analysis comprises 822 companies in the leading subsector of the creative industry in Java. The results showed that all of the characteristics of entrepreneurs and businesses had significant and positive effects on the company’s income. The factors that affected company income are Intellectual Property Rights (IPR) ownerships and the business’s legal status. The primary factor affecting the income was the number of workers. Meanwhile, for each provincial level in Java, it showed that the number of workers, internet use, and the ownerships of IPR had significant and positive effects, while the IPR ownerships had a substantial magnitude in four provincial levels in Java.